Ad-hoc, Mobile, and Wireless Networks 10th International Conference, ADHOC-NOW 2011, Paderborn, Germany, July 18-20, 2011. Proceedings - Frey, Hannes; Li, Xu.; Ruehrup, Stefan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 10th International Conference on Ad-hoc, Mobile, and Wireless Networks, ADHOC-NOW 2011 held in Paderborn, Germany, July 18-20, 2011. The 23 revised full papers presented together with 4 invited papers were carefully reviewed and selected from 53 submissions. The papers are organized in topical sections on routing and activity scheduling, topology control, medium access control, security, mobility management and handling, applications and evaluation, and analytical considerations.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information storage and retrieval systems; Information systems; Information Systems; Telecommunication; Computer Science; Computer Communication Networks; Information Systems Applications (incl.Internet).; Communications Engineering, Networks; Management of Computing and Information Systems; Software Engineering; Information Storage and Retrieval